SUNDEL: REINTERPRETASI BUNGA SEDAP MALAM DALAM MOTIF BORDIR DAN SULAM - Hidayati, Nurul; Sukerta, Pande Made; Supriyanto, Eko; Pamardi, Silvester (Narada : Jurnal Desain dan Seni, 2023)
The making of embroidery and needlework motifs on art-wear that inspired from Sedap Malam (Sedap Malam) is the attempt to create an exclusive embroidery and needlework motifs as the identity of Pasuruan Regency, East Java. The creation of this motifs is the response from the need to develop, enrich, and design an embroidery and needlework motifs belongs to Pasuruan that would boost the sustainability of embroidery and needlework industry that is lately decreasing. Therefore, an experiment method in the form of innovative re-production is required to create an art-work with re-interpretation concept. The method in art creation used in this study is artistic research where the artist undergo several practices or creating process in the field study with emic approach, In this case, the process are developing the local potential in Pasuruan Regency (Sedap Malam) and identify what and how meaning inside it. The creation sages consist of data collection from various resources like field data and direct observation on Sedap Malam, literary study, and extensive interview with Tourism and Culture Department of Pasuruan Regency. The next stage is experimenting tuberose motif using reinterpretation concept. The motifs created during the experiment are stillation of Sedap Malam as the main motif, as well as complementary motifs generated from flora in the surrounding such as pandan leaves and rose balsam flower as the flower commodity in Pasuruan Regency. The inspiration in using Sedap Malam in creating embroidery and needlework motif on ready to wear results to ready to wear design with Sedap Malam motif that is made using embroidery and needlework technique, where Sedap Malam is presented as the main motif in the ready to wear.